Continuous low dose rate irradiation of the rat brain - Madhoo, Jitesh (Division of Radiation Oncology, 2018)
The reported median survival time for patients who are diagnosed with high grade astrocytomas and who undergo postoperative radiotherapy is of the order of 24 to 40 weeks. The course of radiotherapy administered to these patients takes up a considerable portion of their expected survival time. Therefore, any means of reducing the treatment time may contribute to an enhanced quality of life for these patients. A potentially useful method for the reduction of the treatment time may be achieved with the use of continuous low dose rate external beam radiotherapy, where the treatment is administered over a 12 to 24 hour period. A relationship between fractionated and continuous low dose rate irradiation has been reported for skin, however, no such relationship has been reported for the brain. Low dose rate protocols that are equivalent in effect to fractionated (conventional) protocols can be derived using the linear quadratic theory, provided that quantitative radiobiological data for normal tissue (brain) is known. Thus, the aim of the current study is to test the radiation tolerance of the rat brain to low dose rate and fractionated radiation in order to establish the values for the parameters of the linear quadratic model.